2020
DOI: 10.1587/transinf.2020edl8076
|View full text |Cite
|
Sign up to set email alerts
|

SCUT-AutoALP: A Diverse Benchmark Dataset for Automatic Architectural Layout Parsing

Abstract: Computer aided design (CAD) technology is widely used for architectural design, but current CAD tools still require high-level design specifications from human. It would be significant to construct an intelligent CAD system allowing automatic architectural layout parsing (AutoALP), which generates candidate designs or predicts architectural attributes without much user intervention. To tackle these problems, many learning-based methods were proposed, and benchmark dataset become one of the essential elements f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…We employ an FFN for inter-level connection classification. • Intra-level connection: Intra i ∈ {0, 1} 4 , defined in the same way as inter-level connections. Similar to inter-level connections, there are 16 connection types.…”
Section: Node Predicationmentioning
confidence: 99%
See 1 more Smart Citation
“…We employ an FFN for inter-level connection classification. • Intra-level connection: Intra i ∈ {0, 1} 4 , defined in the same way as inter-level connections. Similar to inter-level connections, there are 16 connection types.…”
Section: Node Predicationmentioning
confidence: 99%
“…Previous works have either focused solely on floorplan semantic recognition, neglecting structural reconstruction [ZLYF19, LWG*21], or leaved structural reconstruction as a secondary stage [LWKF17, LZYZ21], relying heavily on heuristic post‐processing or additional optimization. In addition, the floor‐plan dataset also remains one of the main challenges, with existing publicly available datasets having either insufficient floor‐plan samples [LSK*15, LLC*20, LWKF17] or poor data quality [KYH*19], limiting the use and performance of deep neural networks. [LZYZ21] introduces a dataset comprising 7,000 annotated residential floorplans.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases the drawing function outputs a drawing conditioned on the encoded input with some perturbation. Finally, an apartment layout drawing function was implemented based on the SCUT-ALP dataset (Liu et al, 2020) which uses Pix2Pix (Isola et al, 2018) to predict apartment layouts given a footprint.…”
Section: System Designmentioning
confidence: 99%
“…Constructing intelligent computer aided design (CAD) that achieves automatic layout design generation (LDG) with minimum manual adjustment is significant for architectural design. Recently, the problem of LDG has attracted evergrowing research interests in the field of computer vision and graphics [1]- [6] and these works have shown that automatic LDG is possible by learning from data.…”
Section: Introductionmentioning
confidence: 99%
“…The task of LDG aims to produce layout design can- subset II for urban plan in SCUT-AutoALP dataset [1], respectively; (c) shows samples for floor plan generation in RPLAN dataset [2].…”
Section: Introductionmentioning
confidence: 99%